2017
DOI: 10.5812/asjsm.14315
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Perceptive and Cognitive Function Under the Stress of Match in Female Futsal Players

Abstract: Background: Many studies have shown that stress adversely effects cognitive function. However, the effect of acute mental stress is not well understood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…32,56 Finally, for cognitive performance, studies used video tests to evaluate decision-making 20 and other laboratory tests that provide cognitive skills measurements. 50,54…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…32,56 Finally, for cognitive performance, studies used video tests to evaluate decision-making 20 and other laboratory tests that provide cognitive skills measurements. 50,54…”
Section: Discussionmentioning
confidence: 99%
“…without mental fatigue induction) and an experimental one (i.e. with mental fatigue induction), to examine how mental fatigue affects the performance of soccer players 11,20,21,31,32,[49][50][51]54,55 .…”
Section: Focusmentioning
confidence: 99%
See 2 more Smart Citations
“…6 In general, the literature in the last 7 years has shown that sporting excellence and the pursuit of high performance have been the fruits of research that has been gradually developing, especially in female athletes. [7][8][9][10][11][12][13] For investigating the physical and anthropometric profile of futsal athletes is relevant, since it can serve to characterize the body dimensions of elite and non-elite athletes. 14 Furthermore, knowledge of body composition and physical condition are essential for the proper development of sports performance.…”
mentioning
confidence: 99%